Transmission of Turnip yellows virus by Myzus persicae Is Reduced by Feeding Aphids on Double-Stranded RNA Targeting the Ephrin Receptor Protein - Mulot, Michaël; Monsion, Baptiste; Boissinot, Sylvaine; Rastegar, Maryam; Meyer, Sophie; Bochet, Nicole; Brault, Véronique (Frontiers in Microbiology, 2018)
Aphid-transmitted plant viruses are a threat for major crops causing massive economic loss worldwide. Members in the Luteoviridae family are transmitted by aphids in a circulative and non-replicative mode. Virions are acquired by aphids when ingesting sap from infected plants and are transported through the gut and the accessory salivary gland cells by a transcytosis mechanism relying on virus-specific receptors largely unknown. Once released into the salivary canal, virions are inoculated to plants, together with saliva, during a subsequent feeding. In this paper, we bring in vivo evidence that the membrane-bound Ephrin receptor (Eph) is a novel aphid protein involved in the transmission of the Turnip yellows virus (TuYV, Polerovirus genus, Luteoviridae family) by Myzus persicae. The minor capsid protein of TuYV, essential for aphid transmission, was able to bind the external domain of Eph in yeast. Feeding M. persicae on in planta- or in vitro-synthesized dsRNA targeting Eph-mRNA (dsRNAEph) did not affect aphid feeding behavior but reduced accumulation of TuYV genomes in the aphid’s body. Consequently, TuYV transmission efficiency by the dsRNAEph-treated aphids was reproducibly inhibited and we brought evidence that Eph is likely involved in intestinal uptake of the virion. The inhibition of virus uptake after dsRNAEph acquisition was also observed for two other poleroviruses transmitted by M. persicae, suggesting a broader role of Eph in polerovirus transmission. Finally, dsRNAEph acquisition by aphids did not affect nymph production. These results pave the way towards an ecologically safe alternative of insecticide treatments that are used to lower aphid populations and reduce polerovirus damages.